Trends in the Management of Cerebrovascular Diseases (Acta Neurochirurgica Supplement,, 2018)
This is a proceeding book of 8th European-Japanese Cerebrovascular Congress (held in Zurich in 2016). Since many experts from Europe and Japan had very important and fruitful discussion on the management of cerebrovascular diseases, the proceeding book will be very attractive for the physicians and scientists of the area. .